Perceived Neighborhood Crime Safety Moderates the Association Between Racial Discrimination Stress and Chronic Health Conditions Among Hispanic/Latino Adults - Budd, Elizabeth L.; Giuliani, Nicole R.; Kelly, Nichole R. (Frontiers in Public Health, 2021)
Background: Little is known about the link between perceived neighborhood walkability and prevalence of chronic disease. Even less is known regarding this association among Hispanic/Latino adults, despite exhibiting high rates of chronic diseases. Stress due to racial discrimination is a harmful social determinant of health in Hispanics/Latinos. Having both low perceived neighborhood walkability and high racial discrimination stress may exacerbate the chronic disease status of Hispanics/Latinos. Among a U.S. national sample of Hispanic/Latino adults, this cross-sectional study aims to examine 1) the associations among overall perceived neighborhood walkability, racial discrimination stress, and having a chronic health condition; and 2) whether overall perceived neighborhood walkability moderates the hypothesized association between racial discrimination stress and having a chronic health condition. Methods: In January 2018, 798 Hispanic/Latino adults (M age = 39.7 years, SD = 15.1; 58.6% female; 70.0% U.S. born; 52.0% Mexican/Mexican American) responded to a survey via Qualtrics Panels. Surveys included the Neighborhood Environment Walkability Scale-Abbreviated, Hispanic Stress Inventory-2, and self-reported chronic health conditions. Logistic regression was conducted testing for moderating effects of overall perceived neighborhood walkability on the association between racial discrimination stress and having a chronic health condition. Results: After controlling for age, body mass index, and income, racial discrimination stress was inversely associated with overall perceived neighborhood walkability (b = -.18, p < .001) and positively associated with having a chronic health condition (OR = 1.02; 95% CI [1.00, 1.03]). While overall perceived neighborhood walkability was not associated with having a chronic health condition, perceived crime safety was inversely associated with having a chronic health condition (OR = 0.94; 95% CI [0.89, 0.99]). Perceived crime safety moderated the positive association between discrimination stress and having a chronic health condition, as the association was only significant among those who perceived their neighborhood to be less safe (β = -.004, 95% CI [-.01, -.00]). Conclusions: Overall perceived neighborhood walkability was inversely associated with racial discrimination stress, but not associated with having a chronic health condition. Perceived neighborhood crime safety, not infrastructure or aesthetics, matters in the link between racial discrimination stress and having a chronic health condition among Hispanics/Latinos.